L'hétérogénéité de l'enseignement postsecondaire, la diversité de l'intervention publique et les effets redistributifs au Québec - Lemelin, Clement (Canadian Journal of Higher Education, 1992)
The main purpose of this paper, which deals with redistribution effects of public spending on post-secondary education, is to emphasize the importance of accounting for the various forms of public intervention and the differences in its value for students and their families. The CEGEPs and universities are distinguished and three types of public intervention are considered: subsidies to institutions, student aid and tax expenditure. The correlation between social origin and the value of subsidies can change the direction of redistribution effects: students do not register part-time or full-time, nor do they opt for a * program randomly and independent of their social origins. Redistribution effects are shown to be different for college and university.